Dirâsah Badî‘iyyah fî Al-Qasîdah Ar- Ratsâiyyah Dhaj’ah al-Maut Raqdah li Abî Al- ‘Alâ’ Al- Ma‘arriy - Hidayah, Ni’matul; Abidin, Mohammad Khoirul; Yuliani, Antin Rista; Choirunnisa, Akasyah Kunthum (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
The high value of literature is not only found in the Qur’an, but can also be found in the poems created by Arab poets. At the time of the Abbasid era there was a poet who had a high ability to imagine, every poem he had contained a deep philosophical meaning, he was Abū al-ʿAlāʾ al-Ma‘arrī. One of his poems is ‘Dhaj’atu al-Mauti Raqdatun’ which discusses human life and death. This poem is the result of Abu Ala's lamentation after the death of his beloved teacher. The sentences contained in this poem can make the listener dissolve in their beauty. The purpose of this study is to reveal all the beauty of the sentences in the lament this poem by analyzing the science of balaghah precisely in the study of badi'. And one can know how to beautify the kalam by emphasizing the sentences used and the meaning contained therein. This research uses literature study with documentation method for data search, and descriptive method for analysis. After conducting a study in this poem, 115 sentences were found that contained the rules of sentence beauty in it, and 31 forms of muhassinât al-lafziyyah, which took the form of jinâs, saja‘, radd al-‘ajz ‘ala al-shadr, and tasyri’. And 23 sentences of muhassinât al-ma’nawiyyah.